2014
DOI: 10.1016/j.aquatox.2014.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Cellular transport of microcystin-LR in rainbow trout (Oncorhynchus mykiss) across the intestinal wall: Possible involvement of multidrug resistance-associated proteins

Abstract: Please cite this article as: Bieczynski, F., De Anna, J.S., Pirez, M., Brena, B.M., Villanueva, S.S.M., Luquet, C.M.,Cellular transport of microcystin-LR in rainbow trout (Oncorhynchus mykiss) across the intestinal wall: possible involvement of multidrug resistance-associated proteins, Aquatic Toxicology (2014), http://dx.doi.org/10. 1016/j.aquatox.2014.05.003 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early versio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 70 publications
(88 reference statements)
0
21
1
Order By: Relevance
“…More than 80 structural variants have been identified, differing primarily in two L -amino acids. The major isoforms are microcystin-LR (MC-LR), microcystin-RR, and microcystin-YR [ 2 ]. Toxins are released into the surrounding medium during senescence and lysis of bloom cells, which affect many organisms, from terrestrial mammals to algae.…”
Section: Introductionmentioning
confidence: 99%
“…More than 80 structural variants have been identified, differing primarily in two L -amino acids. The major isoforms are microcystin-LR (MC-LR), microcystin-RR, and microcystin-YR [ 2 ]. Toxins are released into the surrounding medium during senescence and lysis of bloom cells, which affect many organisms, from terrestrial mammals to algae.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Schwarzenberger et al (2014) recently reported that the increases of permeases gene expression were detected in the tolerant Daphnia clone, leading to higher production of transporter protein, which subsequently results in a stronger excretion of microcystins from the cells. Given that excreting microcystins process is energy-dependent (Campos and Vasconcelos, 2010;Bieczynski et al, 2014), it is reasonable that elevated Dm-AK expression and ATP content may promote microcystins excretion. Hence, our results together with results of Schwarzenberger et al (2009Schwarzenberger et al ( , 2014 could partly explain why subsequent offspring had higher fitness when the previous generation had been exposed to toxic Microcystis.…”
Section: Discussionmentioning
confidence: 99%
“…3). It is known to us that MCs themselves cannot readily diffuse through the plasma membrane and enter cells without the help of any transporter located in the cell membrane due to their relatively higher molecular weight (900-1100 Da) and moderate hydrophobicity (Komatsu et al, 2007;Bieczynski et al, 2014). Previous studies have found that MC-LR is usually transported into cells via OATPs; for example, OATP1B1 and OATP1B3 are the most efficient MC-LR transporters in human hepatocytes (Hagenbuch and Gui, 2008;Kalliokoski and Niemi, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Transporters such as P-glycoprotein (Pgp, MDR1, ABCB1) and multidrug resistance proteins (MRPs, ABCC) are members of the ATP-binding cassette (ABC) superfamily, and they have been identified in tumor cells to resist drugs or chemicals by immediate discharge and therefore prevention of cell abidance of the drugs or chemicals (Bolhuis et al, 1997;Keppler et al, 2011;Bieczynski et al, 2014).…”
Section: Discussionmentioning
confidence: 99%